Determinants of Men's Involvement in Maternity Care in Dodoma Region, Central Tanzania - Nyasiro S. Gibore; Mangi J. Ezekiel; Alfred Meremo; Mariam J. Munyogwa; Stephen M. Kibusi (Hindawi Limited, 2019)
Background. Men's involvement in maternity care is recognized as a key strategy in improving maternal health and accelerating reduction of maternal mortality. This study investigated the factors determining men's involvement in maternity care in Dodoma Region, Central Tanzania. Methods. This cross-sectional survey used multistage sampling in four districts of Dodoma Region to select 966 married men participants aged 18 years and above. Data were collected using a structured questionnaire. Multivariate logistic regression analysis was carried out in SPSS version 21.0 to measure the determinants of men's involvement in maternity care. Results. The study found that only 1 in 5 men were involved in maternity care of their partners. Factors found to determine men's involvement in maternity care were having >4 children (AOR=1.658, 95%CI=1.134 to 2.422), urban area of residence (AOR=0.510, 95%CI=0.354 to 0.735), waiting time >1 hour at the health care facility (AOR=0.685, 95%CI=0.479 to 0.978), limited access to information (AOR=0.491, 95%CI=0.322 to 0.747), and limited spousal communication (AOR=0.3, 95%CI=0.155 to 0.327). Conclusions. Long waiting time to receive the service and limited access to information regarding men's involvement are associated with low men's involvement in maternity care. Male friendly maternity care should recognize men's preferences on timely access to services and provide them with relevant information on their roles in maternity care. Spousal communication is important; mothers must be empowered with relevant information to communicate to their male partners regarding fertility preferences and maternity care in general.